A comparison of country-level data from the VISIONARY study examining treatment outcomes with preservative-free tafluprost/timolol fixed-dose combination therapy. (3rd July 2022) - Holló, Gábor; Kirwan, James; Lopez-Lopez, Fernando; Zimina, Marina; Fassari, Claudia; Oddone, Francesco; ,
Abstract: Objective: Analysis and comparison of country-level data from the VISIONARY study, examining treatment outcomes with the topical fixed-dose combination of preservative-free tafluprost (0.0015%) and timolol (0.5%) (PF tafluprost/timolol FC) in adults with open-angle glaucoma (OAG) and ocular hypertension (OHT) who were insufficiently treated with or unable to tolerate either beta-blocker or prostaglandin analogue (PGA) topical monotherapy. Methods: A European, prospective, observational study was conducted in 11 countries. Adults with OAG/OHT were switched to the PF tafluprost/timolol FC from either PGA or beta-blocker topical monotherapy. Statistical analysis examined changes in mean standard deviation (SD) intraocular pressure (IOP) from baseline at Week 4, Week 12 and Month 6. Data were documented for each eye separately at baseline and during follow up visits, with the eye reported to have the higher IOP (mmHg), as measured using Goldmann applanation tonometry, being selected for analysis (study eye). Country-level subanalysis examined outcomes by prior monotherapy, diagnosis and timing of dosing for those countries recruiting ≥20 patients (Country-level Subanalysis Population). Two-sided paired t -test was used to assess significance regarding mean IOP reduction from baseline and a compound symmetry covariance model was used in cross-country comparisons regarding variation in IOP change from baseline. Treatment-related adverse events (AEs) were evaluated. Results: Mean (SD) age among patients recruited to the VISIONARY study ranged between 63.9 (11.8) and 72.4 (10.6) years across all countries. The majority of participants (>50%) were female in each country. The Country-level Subanalysis Population included 551 eyes. Mean (SD) IOP was significantly reduced from baseline in each country at Week 4, Week 12 and Month 6 ( p  < .0001). Mean IOP reduction at Month 6 ranged from 5.0 mmHg (22.6%, Hungary) to 7.8 mmHg (31.8%, Latvia) and varied significantly between countries ( p  < .001). The greatest reductions were in Latvia and Russia, where baseline IOP was highest. Country-level IOP reductions were significant irrespective of prior monotherapy, diagnosis or dosing time ( p  < .0001). Most treatment-related AEs occurred in the UK (26 events, 73% mild). One serious AE was reported (Russia, status asthmaticus). Tolerability with PF tafluprost/timolol FC therapy was rated as good/very good by most patients (85.7–100%) in all countries. Conclusion: Subanalysis of VISIONARY study data revealed significant IOP reductions following a switch to the PF tafluprost/timolol FC from either PGA or beta-blocker topical monotherapy. Cross-country variation was likely due to baseline IOP differences. Within country, outcomes were consistent regardless of diagnosis, dosing or prior monotherapy. Treatment was generally well tolerated.